Exploring Barriers to and Facilitators of Physical Activity among Korean American Women. (September 2021) - Choi, JiWon; Cho, Juhyun; Shin, Nah-Mee; Tsoh, Janice
Physical inactivity is prevalent among ethnic minority women including Korean American (KA) women. We explored the barriers to and facilitators of physical activity (PA) and strategies to promote continued engagement in a PA program with a component of an online community. We conducted a qualitative descriptive study of 37 KA middle-aged women who used to be physically inactive and participated in an exit interview following postintervention visit. Using a thematic analysis approach to analyze the data, we found the individual, interpersonal, and neighborhood/community-level barriers to and facilitators of PA; social influence and social support-related themes were evident. Participants expressed benefit and interest in lifestyle modification using social media. Such program that reduces the barriers and reinforces the facilitators may be able to help motivate KA women to increase their PA.